1988
DOI: 10.1180/minmag.1988.052.367.02
|View full text |Cite
|
Sign up to set email alerts
|

The Tertiary Kærven Syenite Complex, Kangerdlugssuaq, East Greenland: Mineral Chemistry and Geochemistry

Abstract: The K~erven syenite complex, which reflects the hitherto earliest recorded stages in the Tertiary of East Greenland, outcrops in the middle reaches of the Kangerdlugssuaq Fjord as a peripheral intrusion to the Kangerdlugssuaq intrusion. The rocks of the K~erven complex range from syenite through alkali feldspar quartz-syenite to alkali feldspar granite. The general sequence of crystallization of the K~erven magmas was: alkali feldspar + olivine(Fa96_99 ) + plagioclase(An41_10, clinopyroxene (augite, ferrosalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Accordingly, it is concluded that: (a) At least two groups of syenites and granites occur at Kaerven and as no single coherent trend is shown they may not be comagmatic. (b) The major mineralogical and chemical differences which are claimed between all the syenites and granites of the K~erven syenite complex and the Kangerdlugssuaq intrusion and other satellite intrusions are not shown by the chemical data in Holm and Pr~egel's paper, nor by the presented mineralogical observations of Holm andPr~egel (1988}~i~r Deer andKempe (1976). Some groups of rocks appear common to all the intrusions.…”
Section: Age Of the Kcerven Syenite Complex Thementioning
confidence: 77%
See 1 more Smart Citation
“…Accordingly, it is concluded that: (a) At least two groups of syenites and granites occur at Kaerven and as no single coherent trend is shown they may not be comagmatic. (b) The major mineralogical and chemical differences which are claimed between all the syenites and granites of the K~erven syenite complex and the Kangerdlugssuaq intrusion and other satellite intrusions are not shown by the chemical data in Holm and Pr~egel's paper, nor by the presented mineralogical observations of Holm andPr~egel (1988}~i~r Deer andKempe (1976). Some groups of rocks appear common to all the intrusions.…”
Section: Age Of the Kcerven Syenite Complex Thementioning
confidence: 77%
“…IN a recent paper Holm and Pr~egel (1988) have described the syenites and alkaline granites of the K~erven syenite complex from the lower Tertiary magmatic province of East Greenland. The province developed during the early stages of the opening in the North Atlantic (e.g.…”
mentioning
confidence: 99%
“…The Greenland plume is equated with major North Atlantic doming and uplift at 65£5Ma prior to rifting and extensive volcanism after 63Ma (White and McKenzie, 1989;Hill, 1991;Lewis et al, 1992). A proposed starting plume generated melts over an area 2,500km in diameter and passed southwards where 58Ma syenite of hotspot character is intruded near Kaerven (Holm and Praegel, 1988) and massive volcanism and spreading took place 200kms further south (White, 1993). The K/T plume position may be marked by intense alkali dolerite dyke injection and bimodal basaltic and alkaline volcanism (64+3Ma) in northern Greenland (Kap Washington Volcanics) (Brown et al, 1987).…”
Section: Proviso (C)mentioning
confidence: 99%